-5x=18-3x

Simple and best practice solution for -5x=18-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x=18-3x equation:


Simplifying
-5x = 18 + -3x

Solving
-5x = 18 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-5x + 3x = 18 + -3x + 3x

Combine like terms: -5x + 3x = -2x
-2x = 18 + -3x + 3x

Combine like terms: -3x + 3x = 0
-2x = 18 + 0
-2x = 18

Divide each side by '-2'.
x = -9

Simplifying
x = -9

See similar equations:

| 0.8m=80 | | -6+4y=-12 | | 5x-4(x-6)=1 | | h=-16t^2+150t+1 | | 2x+y=10-3x | | 2x^2-15x+15=8-x^2-5x | | (u+3)2=2u+11u+15 | | X^4-7x+3=0 | | 2x^4-7x+3=0 | | 2x+3x-15=25 | | -2+x-4x=11 | | 5(6)+3(7)= | | -4+3x=-12+25xfraction | | 2y-4*0=10 | | x-2 = 9 (4-10x)4 | | 9y-5y-9=48.80 | | W-8=23 | | 2y+-4*-2=10 | | -42=-6(z-3) | | 5x+9=82-8x | | -3k^2g-[4kg^2-(6k^2g-2kg^2)]=0 | | 3x-3y+3=2 | | Log(3t+1)=5 | | 49=17(t+1) | | 14abc-[3ab^2c+(4a^2bc)-(-3ab^2c-5abc+5a^2bc)]=0 | | -3y+3=2 | | 3.8=m+9.7 | | -3y+3=0 | | 14abc-[3ab^2+(4a^2bc)-(-3ab^2c-5abc+5a^2bc)]=0 | | -3y-3=0 | | E-5=-13 | | 2-s=9 |

Equations solver categories